How Could Robots Challenge Humans - Dai, Rongqing (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2016)
For the issue whether robots might challenge humans in the future, people have so far focused on the possibility of creating a robot that could be considered as a human in the sense that it could indeed think as a human instead of being solely a tool of humans operated with programmed instructions. Based upon this line of thought it seems that we do not need to worry about the threat of robots since nobody could yet provide any plausible evidence that it is possible to produce this type of robots. However, this way of thinking is philosophically wrong since the fundamental factor to enable robots to challenge humans would be their sociability once they are infused certain level intelligence. This writing would propose the criteria for robots to be considered as sociable and discuss how the robots would pose potential threats to humans.